COLLABORATION BETWEEN ACADEMICS AND LOCAL GOVERNMENTS IN PREPARING POLICIES TO Ease Doing Business for MSMEs IN THE RIAU ISLANDS - Ngaliman; Bambang Satriawan; Edi Indera; Sri Yanti (RADJA PUBLIKA, 2024)
One constraint for business micro small And medium enterprises (SMEs) in start And develop business is lack of convenience effort given​ government in various form its policies . Ease try start from availability information related opportunity business , HR training , fiscal incentives in form loan cost cheap until related marketing the product . In Effort For push development of MSMEs in the Province Riau Islands Academics University Batam ( Uniba ) and Government Province Riau Islands via Service Investment and​ Service Integrated One The door (DPMPTSP) makes an agenda for formulate convenience business that can given all OPDs against MSME actors . Results identification convenience business That will made into material for Provincial Government Riau Islands For make Design Regional Regulations that can give convenience to public Riau Islands in MSME sector . Regulation required Government Province Riau Islands can brave And No doubtful in give convenience try MSME actors according to his authority . Service Investment and​ Service Integrated One Door (DPMPTSP Together with the Academic Team Uniba do visit to a number of office Department / Agency Government at the level province For collect empirical data , and activities that have been they do during This in developing MSMEs. There is around 114 thousand more MSMEs in Kepri.They face a number of challenges , including is expensive logistics And infrastructure . As region islands , MSMEs face uncertainty transportation sea , infrastructure minimal ports , as well as expensive fare send , which increases cost operational . In addition that , they face competition with product outside a larger country cheap , especially through e-commerce, threatening sustainability product local . Capital issues and access financing Also become obstacles . Many MSMEs have difficulty get formal financing because limitations guarantee .